Pengaruh Growth Opportunity, Persistensi Laba, dan Prudence Accounting terhadap Earnings Response Coefficient : Resiko Sistematis sebagai Variabel Pemoderasi - Susilawati Susilawati; Dirvi Surya Abbas; Imam Hidayat (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to determine the effect of growth opportunity, earnings persistence, and prudence accounting on earnings response coefficient, with systematic risk as a moderator in manufacturing companies listed on the IDX for the period 2020 - 2024. The research method used is descriptive quantitative with secondary data in the form of sustainability reports and financial reports from 16 companies taken by purposive sampling from a population of 196 companies. The research method used in this analysis is the random effect model. The results of the analysis show that: 1). growth opportunity has a significant positive effect on earnings response coefficient; 2). Earnings persistence has a significant negative effect on earnings response coefficient; 3). Accounting prudence has a significant positive effect on earnings response coefficient; 4). Systematic risk can weaken the effect of growth opportunity and earnings persistence on earnings response coefficient; 5).  Systematic risk can strengthen the effect of prudence accounting on earnings response coefficient.